(untitled) (Bangladesh Journal of Urology, 2020)
Purpose: Management of posterior urethral distraction defects are challenging for urologists and need very careful and meticulous dissection for getting a good outcome. Dhaka medical college hospital is a tertiary referral hospital where we receive a lot of cases from different districts. The study was done to observe the outcome of anastomotic urethroplasty for posterior urethral distraction defects. Methods : This was a prospective experimental study. This study was done in a single unit of DMCH urology department by a single surgeon . Those who were suffering from posterior urethral distraction defects with suprapubic catheter in situ were included and underwent anastomotic urethroplasty from the period of January, 2018 to october, 2019. After proper evaluation and counseling all patients underwent perineal anastomotic urethroplasty under spinal anesthesia with 6-8 interrupted suture, using 4/0 vicryl. A 14 Fr Foley catheter was placed in urethral lumen and 16 Fr catheter in SPC site. A latex strip drain was placed for perineal wound. Drain was removed after 48 hours of operation . Patients were usually discharged in between 5th to 7th POD with definite follow up protocol and medications with supra pubic catheters (SPC) and per urethral catheters in situ. On 21 POD urethral catheter was removed. SPC was removed after 7 days if patient can void normally. 1st and 2nd follow up were done at the completion of 3rd and 6th month respectively. The prevalence of post-operative sexual disorders was investigated using the International Index of Erectile Function-5 (IIEF-5) questionnaire during follow-up. If the patient can able to void per urethra in a well manner and Qmax>15 mL/s then repair was defined successful. Result : Success rate of perineal anastomotic urethroplasty for posterior urethral distraction defect was 83.33.%. 18 patients were included in the study. The mean age was 28.27 years. 17 patients were able to void successfully after surgical procedure but among those 2 patients had urinary flow rate < 15 ml/sec and one patient didn’t able to void. 3 patients had developed wound infection, 3 patients developed erectile dysfunction. Conclusion : Perineal anastomotic urethroplasty is gold standard for treatment of posterior urethral distraction defects. Long term follow up is needed to give a opinion regarding the ultimate outcome of the surgical procedure and that have give a good idea for future management. Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.193-198